The forgotten kids: Experiences of potential student-athletes at a postsecondary football preparatory school - Stokowski, Sarah; Bo, Li; Turk, Megan; Fridley, Ali; Hutchens, N. Shelby (Journal of Amateur Sport, 2019)
The first preparatory institution was founded in 1635 to prepare elite men for public service, a role in the church, or admission to Harvard (Boyer, 1983). Nearly 400 years later, the objective of such institutions is no longer Harvard, but often an avenue for potential student-athletes (PSAs) to participate in collegiate sport (Thamel, 2007). The NCAA does not define nor regulate postgraduate preparatory institutions; however, Curran (2014) describes a preparatory institution (commonly referred to as prep schools) as a postgraduate institute that provides PSAs another year at a secondary institution prior to making the transition to college. Framed by Mincer’s (1958) model of Basic Human Capital, the purpose of this study is to examine the experiences of those attending or associated with one specific preparatory institution (X Academy). The first research question which explores prospective student-athletes choices to attend a preparatory institution revealed three final themes: (1) eligibility concerns, (2) athletic exposure and development, and (3) academic improvement. The second research question explores the experiences of those attending a preparatory institution also revealed three final themes: (1) focus and preparation, (2) melting pot, and (3) survival.